RELATIONSHIP OF INTEREST, LEARNING MOTIVATION AND ATTITUDE WITH RESULTS LEARNING CLASS VIII SMP STATE 13 MAKASSAR - Putri Athirah Azis (Universitas Negeri Makassar, 2016)
The study aims at examining (1) the correlation of learning interest towards learning result of grade students, (2) the correlation of learning motivation towards learning result of grade students, (3) the correlation of students attitude towards learning result, (4) the correlationof interest, learning motivation, and attitude collaboratively towards learning result. The study is an ex post facto. The population of the study was grade VIII at SMPN 13 Makassar. Samples were 105 students taken by employing random sampling technique. Data were collected through questionnaire and documentation. Data were analyzed using regression test. The result of study reveal that (1) there is significant correlation (p<0,01) of interest towards learning result of grade VIII students at SMPN 13 Makassar. Co-efficient correlation (r) is 0,718 and its effectiveness contribution (R2) is 51,5%, (2) there is significant correlation (p<0,01) of motivation towards learning result of grade VIII students at SMPN 13 Makassar. Co-efficient correlation (r) is 0,775 and its effectiveness contribution (R2) is 60,1%, (3) there is significant correlation (p<0,01) of attitude towards learning result of grade VIII students at SMPN 13 Makassar. Co-efficient correlation (r) is 0,737 and its effectiveness contribution (R2) is 54,4%, (4) there is significant correlation (p<0,01) of interest, motivation and attitude collaboratively towards learning result of grade VIII students at SMPN 13 Makassar. Co-efficient correlation (r) is 0,861 and its effectiveness contribution (R2) is 74,1%,